Socio-cultural Features of Uzbek People's Games and Performances - Furkatovich, Akromov Hasan (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the historical, ethnographic and socio-cultural features of the Uzbek national folk games and performances, inherited from ancestors. It examines family ceremonies, national sports held at public events, folk games and performances in the past, based on some historical and ethnographic sources, sociological surveys. Such folk games and performances, including "kurash", "kupkari", "racing (poyga)". The historical roots and social aspects of national sports such as “horse racing” are revealed, their socio-spiritual characteristics and their place as an important social issue today are emphasized. Its coverage is also based on written sources of famous scholars who lived in the past. The article describes the measures taken in Uzbekistan in the context of globalization to revive national sports, pass them on to future generations and increase the global prestige of "Uzbek wrestling" as a national sport of the Uzbek people. It describes the need to work today to further improve the work in this area, based on the historical traditions and experience of our ancestors, and the measures taken in this direction. The article provides ethno-historical and sociological analysis of the need to promote the masterpieces of the spiritual culture of the Uzbek people in the context of rapid renewal in society, the need to work based on the historical traditions of our ancestors. The final conclusions on the general content of the article are also given.